Development of Information for Supporting Emergency Respond for Dengue fever Outbreak in Noen Sa-nga District, Chaiyaphum Province in 2020 - ธรรมกุล บุญพิสิฐษ์ (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2021)
A research and development study was conducted. The purposes of the study were 1) To develop an information system for supporting emergency response of dengue fever in the new normal era 2) To study methods for transferring the technology to public health volunteers, and 3) To study the results of using the information system. The study was conducted between January and August 2020. The participants included responsible officers of disease control about 15 persons and 229 village health volunteers. Google form and practice record form were used to survey the opinion for using an information system. Analyzed data by using average and percentage. Content analysis was done. According to the concept of System Development Life Cycle (SDLC), the development required 6 steps 1) Planning 2) Analysis 3) Design 4) Testing and dissemination 5) System installation 6) Development and maintenance. The results indicated that the information system development in a new normal era was designed by using technologies. Facilities were developed for supporting the operations as shown below; google form was used as an online form to collect the data from 2 systems including 1) Reporting 3-3-1 outbreaks 2) Mosquitoes larvae index survey. There were notified via Line group after recording by using Line Notify. Google sheet was designed as the database of patients and mosquitoes’ larvae index. Google site was used to design websites. Google data studio was used to analyze data, and the results were interpreted by graphs and statistics. Workshops were conducted for training technologies for stakeholders. Therefore, they had the knowledge, understand, and skill for using the system at a good level. Users had satisfaction at a high level, those indicated that the system was good, not complicated, convenient, and fast. The system influenced to control the outbreak of dengue fever in the areas effectively.